Practices and values regarding milk consumption among pre-schoolers in Bangkok. Issue 1 (1st January 2018) - Yothasamut, Jomkwan; Camfield, Laura; Pfeil, Michael
ABSTRACT: Purpose : Thai government agencies and the business sector have been promoting milk consumption. Considering the robust and continual movements by those actors to promote milk consumption among children in Thailand at the national level, this study aims to investigate milk-consumption practices and values towards milk consumption at pre-school, family and individual levels. Methods : This cross-sectional qualitative study employs observation and interview methods, along with the Ecological System Theory as a framework. Data were collected from three kindergartens used by families of varying socio-economic status, and the homes of 18 pre-schoolers, aged 3-5 years old, attending these kindergartens, from October 2013-September 2014. Results: Findings reveal kindergartens implemented daily routines to make children drink milk. Practices at home include (i) overfeeding of milk, (ii) preference for fortified milk and (iii) using sweetness to make children drink milk. These practices were underpinned by values that milk is good for children and good parents feed their children milk. These values, in combination with other macro-level measures such as the government's milk-promotion campaigns and the milk industry's marketing, influence the milk-drinking practices of pre-schoolers. Conclusion : The promotion of the benefits of milk prompted children to exceed the recommended milk consumption of 400ml per day. Balanced information on moderation in milk drinking was absent.